STUDENTS’ ERRORS ON WRITING (An Analysis Studies At Junior High School) - Pohan, Albert Efendi (Universitas Riau Kepulauan, 2017)
This research is aimed to:1) describe the students?common errors in writing recount text, 2) classify the most dominant typesof the students? errors in writing recount text at the eighth grade students of SMP N 40 Batam in academic year 2016/2017. The research was conducted on April 2017 which was held at the eighth grade students with the number of sample was 70 students. The researcher gave written test to collect data and the method that was appliedin this research by qualitative method. The result of the research showed the dominant error of classification error in writing recount text was verbs tense error which the percentage was 27.82% with the number 444 errors, 22.43% error of punctuation with the number 358 errors, 14.79% error of unnecessary word with the number 236 errors, 10.84% error of missing word with the number 173 errors, 7.77% error of subject verb agreement with the number 124 errors, 4.51% error of noun singular/plural with the number 72 errors, 4.39% error of word form with the number 70 errors, 3.82% error of sentence fragment with the number 61 errors and 3.63% error of article with the number 58 errors.Keywords: Error Analysis, Writing, Recount Text